Formulasi Sediaan Masker Wajah Ekstrak Labu Kuning (Cucurbita moschata) Bentuk Clay Menggunakan Bentonit dan Kaolin Sebagai Clay Mineral - Santoso, Cynthia C.; Darsono, Farida L.; Hermanu, Liliek S. (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Free radicals can cause oxidative damage that plays a role in the aging process and cause degenerative diseases that appear on the skin, so that antioxidants are needed to reduce the cumulative effects of oxidative damage in the form of clay mask. One of the natural materials that can be used as a clay mask is pumpkin fruit. Beta carotene in the yellow pumpkin can be used as an antioxidant that has a mechanism of electron transfer process so that free radical can be deactivated, and the saponin content in yellow pumpkin was function as cleanser effect. The aims of this study were to determine the effect of the combination of bentonite and kaolin as clay minerals, and to get the optimum composition of the formula. Clay mask formulation was optimized using factorial design with design expert software ver 10.0. Responses used were the viscosity, spreadability, and drying time. The results showed that bentonite give a significant effect to increase the viscosity, decrease spreadability and drying time. Kaolin gives a significant effect to increase the viscosity, decrease spreadability and drying time. The interaction between kaolin and bentonite give significant effect to increase the viscosity, spreadability, and drying time. The optimum formulation of clay mask was obtained with the combination of bentonite 23.95% and kaolin 18.60%, which estimates viscosity 236222 cps; spreadability 4.20 cm; and drying time 14.65 minute.